Analysis of local stakeholders in the collaborative management of “Nahuatlaca – Matlazinca” state park, Mexico - Aguilar Pedraza, Alfonso (2024)
This research is developed from the perspective of shared governance. The purpose of this study is to analyze the collaborative relationships among social actors in San Pedro Techuchulco through the Social Analysis System (SAS-CLIP) to determine their influence on the management of the Nahuatlaca-Matlazinca State Park (PENM), Mexico. The methodology used comprises two phases: the first phase involves characterizing the social actors (identification and categorization profiles of actors); the second phase consists of analyzing the collaborative and/or conflict relationships. According to the results obtained, there is a lack of collaborative management and conflict among the identified actors, which poses an obstacle to establishing and achieving specific objectives that address the needs of the community and the natural resource management of the PENM. The community needs to establish links for decision-making that allow for incorporating collective strategies and fostering community participation within the shared governance framework of protected natural areas.